2023
DOI: 10.1049/sfw2.12099
|View full text |Cite
|
Sign up to set email alerts
|

The impact of feature selection techniques on effort‐aware defect prediction: An empirical study

Abstract: Effort‐Aware Defect Prediction (EADP) methods sort software modules based on the defect density and guide the testing team to inspect the modules with high defect density first. Previous studies indicated that some feature selection methods could improve the performance of Classification‐Based Defect Prediction (CBDP) models, and the Correlation‐based feature subset selection method with the Best First strategy (CorBF) performed the best. However, the practical benefits of feature selection methods on EADP per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…The results indicated that the feature selection technique could enhance the performance of the KNN, MLP, and LR classifiers, with the KNN classifier achieving the best performance with seven features. Li et al [48] give an investigation to discuss how the feature selection method impacts the effort-aware defect prediction task. They construct experiments on 41 PROMISE datasets with 24 feature selection methods and 10 classifiers.…”
Section: Empirical Studies Of Feature Selection Techniquesmentioning
confidence: 99%
“…The results indicated that the feature selection technique could enhance the performance of the KNN, MLP, and LR classifiers, with the KNN classifier achieving the best performance with seven features. Li et al [48] give an investigation to discuss how the feature selection method impacts the effort-aware defect prediction task. They construct experiments on 41 PROMISE datasets with 24 feature selection methods and 10 classifiers.…”
Section: Empirical Studies Of Feature Selection Techniquesmentioning
confidence: 99%
“…In our empirical study, we use the three threshold-dependent evaluation metrics (Precision, Recall, and F-measure (F1)) and one threshold-independent evaluation metric (Matthews correlation coefficient, MCC) to evaluate the performance of CSD models. The metrics are widely used in both software engineering studies [64][65][66][67][68][69][70][71] and artificial intelligence researches. [72][73][74][75] In the binary classification problem, these four evaluation metrics can be calculated according to a confusion matrix, as shown in Table 4.…”
Section: Performance Measuresmentioning
confidence: 99%
“…This helps select suitable algorithms based on software project requirements, addressing ranking instability in EADP studies. Li et al 19 investigated the impact of feature selection methods on EADP. They employed six effort-aware metrics to assess the EADP models' performance comprehensively.…”
Section: Related Workmentioning
confidence: 99%
“…Consequently, Software Defect Prediction (SDP) techniques have garnered significant attention as they enable the optimal utilization of limited resources. Software testing teams construct SDP models based on historical software data to predict the defect proneness of software modules to be inspected 3 . This allows them to allocate testing resources more effectively or prioritize the inspection of those modules that are predicted to have defects, thereby facilitating the efficient allocation of software testing resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation